Coupled Static-Dynamic Tensile Mechanical Properties and Energy Dissipation Characteristic of Limestone Specimen in SHPB Tests. (11th February 2020) - Ping, Qi; Fang, Zhaohui; Ma, Dongdong; Zhang, Hao
Abstract : To investigate the dynamic splitting tensile mechanical property of limestone under coupled static and dynamic state, the dynamic split tensile tests of limestone under one-dimensional coupled static and dynamic load with different strain rates were performed with the help of modified split Hopkinson pressure bar (SHPB) equipment. The dynamic splitting tensile mechanical property and energy dissipation characteristic under two stress states were also compared in this research. Test results indicated that the dynamic tensile strength of the limestone specimen increased with the increase of average strain rate, exhibiting an obvious strain rate effect. In addition, dynamic tensile strength under uniaxial state was higher than that under one-dimensional coupled static and dynamic load state under the same test condition. Moreover, the deformation modulus increased with increasing average strain rate under uniaxial state, while it decreased with increasing average strain rate under coupled static and dynamic state. Both the reflected energy and absorbed energy linearly increased with increasing incident energy. The preload in the radial direction could increase the reflected energy and decrease the absorbed energy. Moreover, the transmitted energy with preload state was slightly lower than that under uniaxial state. Finally, the dynamic tensile strength of limestone specimen increased as a power function with increasing absorbed energy.